Increasing Physical Activity in Children: From Evidence to Action. Issue 4 (July 2015) - Jakubowski, Tami L.; Faigenbaum, Avery D.; Lindberg, Claire
Abstract : Abstract: Daily physical activity has the potential to improve health and well-being, yet worldwide surveillance of physical activity levels indicate a growing number of children and adolescents do not meet current physical activity recommendations. The current symptom-reactive paradigm should be reconsidered, and preventive actions initiated, before inactive children become resistant to targeted interventions and require pharmacotherapy, and expensive medical procedures for treatment of preventable illnesses. A cascade of adverse events are associated with a sedentary lifestyle. Nurses are uniquely qualified to identify youth with exercise deficits and encourage daily participation in a variety of age-related physical activities that enhance both health- and skill-related components of physical fitness. Physical activity guidelines should support evidence-based activity recommendations by nurses working with children. New insights regarding the importance of improving muscular strength and motor skill performance early in life are valuable to nurses in formulating exercise recommendations for school-age youth. Specific education in pediatric exercise science provides the foundation for prescribing age-related exercise interventions consistent with the needs, abilities, and interests of infants, toddlers, children, and adolescents. Given the critical importance of primary prevention, transformational change in the current system for identifying and treating youth with exercise deficits is warranted. Abstract : Physical inactivity is now the fourth leading risk factor for global mortality, yet a growing number of children and adolescents do not meet current physical activity guidelines. Review the latest evidence and guidelines to promote appropriate physical activity in children.